Distributed Control for Coupled Nonholonomic Mobile Robots under the Event‐Triggered and Self‐Triggered Frameworks. Issue 3 (4th November 2016) - Yang, Chengshuai; Qiu, Yilong; Chen, Fei; Xiang, Linying
Abstract: In this paper, a coordinated tracking problem for coupled nonholonomic mobile robots is considered. An event‐triggered control strategy is first proposed to guarantee that the robots can form a prespecified geometric pattern while the centroid of the geometric pattern can track a reference signal. The results are then extended to the self‐triggered case, where continuous monitoring of the agent states is not needed. The stability of the system is proved with the aid of the Lyapunov techniques. Finally, numerical examples are presented to verify the validity of the theoretical results.